2017
DOI: 10.3390/su9040671
|View full text |Cite
|
Sign up to set email alerts
|

How Do Quality Practices Affect the Results?: The Experience of Thalassotherapy Centres in Spain

Abstract: Most thalassotherapy centres in Spain do not have any quality certification but they are carrying out several actions of quality management in an attempt to obtain better results. Consequently, the aim of this research is to study if the implementation of quality practices on thalassotherapy centres has the same impact on companies' results as on the results of those companies that got the quality certifications. In addition, the relationships between different factors considered are going to be studied. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…The early objective of TQM aims to achieve a superior quality of products through the involvement of all functions within the organization to create continuous improvement, which enables firms to exceed customers' expectations [46,47]. García et al [48] indicated that companies implement quality management practices that can influence its result, which enhance service quality. Effects of TQM on financial as well as non-financial performance have been approved by many research studies by characterizing the TQM program into several practices [15,46].…”
Section: Tqm Practices and Flexibilitymentioning
confidence: 99%
“…The early objective of TQM aims to achieve a superior quality of products through the involvement of all functions within the organization to create continuous improvement, which enables firms to exceed customers' expectations [46,47]. García et al [48] indicated that companies implement quality management practices that can influence its result, which enhance service quality. Effects of TQM on financial as well as non-financial performance have been approved by many research studies by characterizing the TQM program into several practices [15,46].…”
Section: Tqm Practices and Flexibilitymentioning
confidence: 99%
“…Empirically, the findings from this study are in agreement with the study of Elhawi (2021) which affirmed that total quality management and competitive advantage, it was discovered that adopting the practices of quality management has a positive effect of competitive advantage as a measure of performance which leads to the progress and prosperity of the company. Álvarez-García et al (2017) found that companies implement quality management practices that can influence its result, which enhance service quality leading to an advantage over competitors. The study of Eniola et al (2019) further confirmed that the adoption of total quality management has an effect on the performance of SMEs and creates a competitive advantage for the firm.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The study of Lan (2017) showed that the objective of quality management practice is to achieve high-quality of products through the involvement of all functions within the organisation, in order to create continuous improvement, which enables firms to exceed customers' expectations and sustain competitive advantage. Álvarez-García et al (2017) found that companies implement quality management practices that can influence its result, which enhance service quality leading to an advantage over competitors. The study of Elsher and Augustyn (2016) reported that even though quality management may be a source of competitive advantage, some variables such as customer focus and employee management are questionable while process management and quality data do not contribute to the achievement of competitive advantage This study, therefore, hypothesizes that: H0: Quality management practices have no significant effect on competitive advantage in the selected Food and Beverage manufacturing companies in Lagos State, Nigeria.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Using the case of thalassotherapy centers as an example, managers should focus on continuous improvement to improve their customers' results. Furthermore, if managers look to improve other outcomes, they need to focus on process management [39]. Organizational culture is essential for continuous improvement [5,40,41].…”
Section: Continuous Process Improvementmentioning
confidence: 99%